Role of accounting in a corporatised public organisation intertwined issues of accountability and trust / Nor Aziah Abu Kasim - Abu Kasim, Nor Aziah (Accounting Research Institute (ARI) & Faculty of Accountancy, 2006)
This paper presents an in-depth case study of a Malaysian public utility undergoing reform to transform itself into a self-financing, and profitable organisation during corporatisation. As profitability became increasingly important, attempts to enhance profitability were made through imposing new budgeting rules and recruiting new accounting graduates. An explanatory case study method, using mainly semi-structured interviews was adopted. The theoretical framework for understanding the process of implementing accounting change, the context in which change unfolded and the emerging consequences of change is based on the insights of new institutional sociology (Meyer and Rowan, 1977). The findings reveal that accounting changes were enacted, but over time became separated from, or loosely coupled with, other intra-organisational concerns. The top-down manner in which the budget targets was imposed by the accountants created tensions and constraints, changes in power relations and a climate of lack of trust. The explanations on the emergence of loosely coupled budget enrich our understanding of why budgeting changes are enacted but the budget is used as rituals for requesting funds rather than for planning and guiding operational decisions.